1997
DOI: 10.1017/s0033822200018816
|View full text |Cite
|
Sign up to set email alerts
|

14C Dating of Terrestrial Moss in Tern Lake Deposits, Antarctica

Abstract: ABSTRACT. Accurate radiocarbon ages were obtained from terrestrial moss from two drill holes in Tern Lake deposits, Antarctica, using liquid scintillation counting (LSC) and accelerator mass spectrometry (AMS). The results show that the lake deposits have been accumulating since the end of the last glacial epoch ca. 12,600 cal BP at the rate of 0.13-1.1 mm a-1. We discuss the validity of 14C ages of Antarctic lake deposits, with respect to the latitude effect of 14C productivity, the reservoir effect, the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The mean sedimentation rate is 0.25 mmyr -1 and oscillates mainly between 0.17–0.33 mmyr -1 , which is in the range of values reported by Shen et al (1998; 0.004–1.1 mm yr -1 ) and very similar to the rates found by Björck et al (1996; 0.25–0.4 mm yr -1 ). Considering that when the climate is warm the catchment area of a lake is ice-free and sediments can be eroded and reach the lake, during warm periods a high sedimentation rate is expected.…”
Section: Discussionsupporting
confidence: 89%
“…The mean sedimentation rate is 0.25 mmyr -1 and oscillates mainly between 0.17–0.33 mmyr -1 , which is in the range of values reported by Shen et al (1998; 0.004–1.1 mm yr -1 ) and very similar to the rates found by Björck et al (1996; 0.25–0.4 mm yr -1 ). Considering that when the climate is warm the catchment area of a lake is ice-free and sediments can be eroded and reach the lake, during warm periods a high sedimentation rate is expected.…”
Section: Discussionsupporting
confidence: 89%
“…using the INTCAL98 calibration data set (Stuiver et al, 1998) in the CALIB 4.4 program (Stuiver and Reimer, 1993); the results are shown in Pb date are illustrated in Figure 2 versus depth. As can be seen from Figure 2, the radiocarbon date of the moss-rich sediment sample G-08 is apparently too old in comparison with the 210 Pb dating results, and this is consistent with the results of Björck et al (1991aBjörck et al ( , 1991b and Shen et al (1998), who suggested that the dates on aquatic moss samples were more reliable than those of the bulk sediments themselves. If G-08 is removed from the age-depth modeling, we see a good correlation between the dates and the sediment depth with a slope or average sedimentation rate of 0.027 cm a…”
Section: Chronologysupporting
confidence: 88%
“…While terrestrial mosses almost exclusively take up atmospheric CO 2 during photosynthesis and give reliable dates (e.g. Shen et al 1998), aquatic (submerged or emergent) mosses can also take up reservoir-aged dissolved inorganic carbon (DIC), yielding radiocarbon dates that can be up to 6000 14 C yr too old (e.g. MacDonald et al 1987;Madeja and Latowski 2008).…”
Section: Spiere Groupmentioning
confidence: 99%